Numerical simulation of methyl linoleate peroxidation inhibited by α-tocopherol - L. A. Tavadyan; Khachoyan, A. A.; G. A. Martoyan; A. Kamal-Eldin (ՀՀ ԳԱԱ հրատ.)
A kinetic model of methyl linoleate peroxidation inhibited by α-tocopherol was constructed. Good accord was obtained with experimental data at 40°C. Model was numerically analyzed by the value method based on Hamiltonian systematization of kinetic equations. The extremal complex behavior of reaction induction period in relation to α-tocopherol initial concentration is related to the increase in the ratios of [tocopheroxyl radical]/[peroxyl radical] and the {tocopherol mediated peroxidation rate}/{rate of termination by combination of tocopheroxyl and peroxyl radicals}. The prooxidant influence of autoinitiation reaction with α-tocopherol and hydroperoxide are important too. Կառուցված է α–տոկոֆերոլով արգելակված մեթիլլինոլեատի պերօքսիդացման ռեակցիայի կինետիկական մոդել: Մոդելը ադեկվատ նկարագրում է 40°C ստացված փորձնական արդյունքները: Ինդուկցիոն ժամանակահատվածի բարդ, ոչգծային կախվածությունը α–տոկոֆերոլի սկզբնական կոնցենտրացիայից բացատրված է [տոկոֆերօքսիլ ռադիկալ]/[պերօքսիլ ռադիկալ] կոնցենտրացիաների և համապատասխանաբար {տոկոֆերոլի խթանմամբ պերօքսիդացման արագություն}/{տոկոֆերօքսիլ և պերօքսիլ ռադիկալների ռեկոմբինացիայի արագություն} հարաբերությունների աճով, ինչպես նաև α-տոկոֆերոլի հիդրոպեչօքսիդի մոլեկուլների մասնակցությամբ ընթացող ինքնահարուցման ռեակցիայով: Построена кинетическая модель реакции перекисного окисления метиллинолеата, ингибированной α-токоферолом. Модель адекватно описывает экспериментальные кинетические данные, полученные при 40°С. Нелинейная, сложная зависимость периода индукции реакции от начальной концентрации α-токоферола объяснена увеличением соотношения концентраций [токофероксильный радикал]/[пероксильный радикал] и соответственно ростом соотношения скоростей {скорость перекисного окисления с участием α-токоферола}/{скорость рекомбинации токофероксильных и перокисльных радикалов}, так же, как и прооксидантным влиянием реакции автоинициирования с участием молекул α-токоферола и гидропероксида.
Keywords: Physical Chemistry